2005
DOI: 10.1089/jmf.2005.8.413
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Lycopene During Food Processing and Storage

Abstract: With an increasing understanding of the health benefit of lycopene, how to preserve lycopene during food processing and storage has caused much attention. Lycopene belongs to the carotenoid family and mostly exists in nature as the all-trans form. Heat, light, oxygen, and different food matrices are factors that have an effect on lycopene isomerization and autooxidation. Lycopene may isomerize to mono- or poly-cis forms with the presence of heat or oil or during dehydration. Reisomerization takes place during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(121 citation statements)
references
References 45 publications
6
102
1
3
Order By: Relevance
“…These days the nutritional and health benefits of lycopene of watermelon juice are well known. Xianquan et al (2005) indicated that, under different food processing conditions, lycopene undergoes degradation via isomerization and oxidation, which impact its bioactivity and reduce the functionality for health benefits. Therefore, food processing technologies should ensure the availability of sufficient amount of lycopene after a given thermal process.…”
Section: Temperature Stability Of Vitamin C and Lycopenementioning
confidence: 99%
See 1 more Smart Citation
“…These days the nutritional and health benefits of lycopene of watermelon juice are well known. Xianquan et al (2005) indicated that, under different food processing conditions, lycopene undergoes degradation via isomerization and oxidation, which impact its bioactivity and reduce the functionality for health benefits. Therefore, food processing technologies should ensure the availability of sufficient amount of lycopene after a given thermal process.…”
Section: Temperature Stability Of Vitamin C and Lycopenementioning
confidence: 99%
“…The carotenoid content varies depending on the variety of the watermelon. Depending on the variety, carotenoid content in red fleshed watermelon varies from 37 -121 mg/kg fresh weight, where as lycopene varies from (23.0-72.0µg/g of weight) (Xianquan et al, 2005). Carotenoids have antioxidant activity and free-radical scavenging property.…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is highly active on reactive singlet oxygen ( 1 O2) and is the most effective antioxidant among carotenoids (Woodall et al, 1997;Henry et al, 1998). The oxidation of lycopene causes loss of color (Xianquan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive medical researchers reported that lycopene helps the human body fight against different types of cancers (prostate, breast), atherosclerosis and reduce blood cholesterol levels (Kerkhofs et. al., 2005;Xianquan et al, 2005). Tomato cultivation is highly seasonal, huge quantities are available at right season of the year.…”
Section: Introductionmentioning
confidence: 99%